Spontaneous and Stimulated Emission Spectra for the Molecule ¹²⁴Xe³⁵Cl. - Zubrilin, N.G.; Osypov, S.I.; Pavlov, I.A.; Chernomorets., M.P.; Baschenko, S.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The influence of the isotopic composition of active medium on a lasing spectrum of a XeCl laser has been investigated. Spectra of spontaneous and stimulated emissions for monoisotopic ¹²⁴Xe³⁵Cl molecules were measured. The frequencies in lasing spectrum were determined. The frequencies of vibrational edging in the luminescence spectra of the molecule ¹²⁴Xe³⁵Cl. l were also measured. We showed that varying the isotopic composition of the active medium one can get the lasing on frequencies different from the lasing ones in the natural XeCl laser.